2004
DOI: 10.1363/3605804
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Intentions of Future Health Care Providers Toward Abortion Provision

Abstract: 58Perspectives on Sexual and Reproductive Health attending the University of Washington and their intention to provide abortion services in their practices. The primary outcome of this study was students' intention to incorporate abortion into their practice. Secondary outcomes were willingness to seek abortion training and attitudes toward advanced clinical practitioner provision of abortion services. On the basis of previous work, we hypothesized that students in medical programs, those in women's health-ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 10 publications
4
34
0
2
Order By: Relevance
“…In summary, the majority of medical students in this cohort were moderately/strongly prochoice, and stated beliefs that were generally congruent with their peers internationally, for example, the UK, Norway, South Africa and Malaysia 8 13 18 21. However, it should be noted that cultural differences between Irish and North American students were apparent in this study, whereby medical students from North America were largely in favour of TOP being legally available on request, while Irish students (although similarly identified as predominantly moderately/strongly prochoice) expressed less support for TOP on request and to a greater extent favoured TOP under certain circumstances only.…”
Section: Discussionmentioning
confidence: 80%
“…In summary, the majority of medical students in this cohort were moderately/strongly prochoice, and stated beliefs that were generally congruent with their peers internationally, for example, the UK, Norway, South Africa and Malaysia 8 13 18 21. However, it should be noted that cultural differences between Irish and North American students were apparent in this study, whereby medical students from North America were largely in favour of TOP being legally available on request, while Irish students (although similarly identified as predominantly moderately/strongly prochoice) expressed less support for TOP on request and to a greater extent favoured TOP under certain circumstances only.…”
Section: Discussionmentioning
confidence: 80%
“…Most of the studies identified gestational limits only with regard to early- or late-stage abortion with minimal barriers to first-trimester abortion reported in four studies 2 37 41 52. In the USA, although 98% of the facilities provided services to women up to and including 8 weeks’ gestation, fewer than half provide services at 13 weeks and many set limits between 11 and 12 weeks 2.…”
Section: Resultsmentioning
confidence: 99%
“…[11][12][13][14][15][16] In addition, research at individual medical schools has shown that a majority of students planning to go into family medicine and related fields believe that induced abortion training should be available during residency. 17,18 To meet the needs of family medicine trainees, an adequate percentage of family physician educators must have experience in the management of EPF and abortion. Limited data exist regarding the provision of EPF management in family medicine.…”
Section: Cine (Stfm) Group On Hospital and Proceduralmentioning
confidence: 99%